Semantic analysis algorithm of text information - Сич, М. Ю. (Problems of Informatization and Control, 2009)
Description of an analysis algorithm of the text information on a basis two level encodings of words is resulted. The basic concepts of semantic processing of the information and processes of definition of contextual senses of words and connections between them are resulted